1993
DOI: 10.1037/0021-843x.102.1.133
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent psychopathology: I. Prevalence and incidence of depression and other DSM-III—R disorders in high school students.

Abstract: Data were collected on the point and lifetime prevalences, 1-year incidence, and comorbidity of depression with other disorders (Diagnostic and Statistical Manual of Mental Disorders [3rd ed., rev.]) in a randomly selected sample (n = 1,710) of high school students at point of entry and at 1-year follow-up (n = 1,508). The Schedule for Affective Disorders and Schizophrenia for School-Age Children was used to collect diagnostic information; 9.6% met criteria for a current disorder, more than 33% had experienced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

94
1,122
15
28

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,510 publications
(1,259 citation statements)
references
References 62 publications
94
1,122
15
28
Order By: Relevance
“…For example, the average duration of an episode of major depression is 6 months. 18,19 It is possible that eating disorders, particularly BED, may simply show a shorter course. Perhaps individuals will only tolerate these eating disorders for a certain duration before the subjective distress motivates them to seek treatment or discontinue these behaviors on their own.…”
Section: Long-term Stability Of Eating Disorder Diagnoses (Fichter Andmentioning
confidence: 99%
“…For example, the average duration of an episode of major depression is 6 months. 18,19 It is possible that eating disorders, particularly BED, may simply show a shorter course. Perhaps individuals will only tolerate these eating disorders for a certain duration before the subjective distress motivates them to seek treatment or discontinue these behaviors on their own.…”
Section: Long-term Stability Of Eating Disorder Diagnoses (Fichter Andmentioning
confidence: 99%
“…This overlap is observed at the level of mood, symptoms, and disorder for many of the most common psychiatric disorders among youth, including anxiety, conduct/oppositional defiant, and attention deficit/hyperactivity (ADHD) (Costello et al 2003;Lewinsohn et al 1993;Newman et al 1998; see Hankin and Abela 2005;Rudolph et al 2006, for reviews). For example, a meta analysis (Angold et al 1999) of depression comorbidity with these other symptoms and disorders among community samples revealed that depression was associated with anxiety (median odds ratio=8.2), conduct/oppositional problems (median odds ratio=6.6), and ADHD (median odds ratio=5.5).…”
Section: Introductionmentioning
confidence: 99%
“…Diagnostic Interview-The K-SADS interview was conducted with the adolescents to obtain current and lifetime diagnoses. Parents did not participate in the diagnostic assessment both because of the already lengthy nature of our assessment and because, as noted by others (Lewinsohn et al, 1993), the reliability of adolescent report increases and the agreement between parent and adolescent decreases with age. Additionally, our primary focus was on depressive symptomatology and we expected that adolescents would have more direct access to information regarding their depressive moods and behaviors.…”
mentioning
confidence: 96%
“…Additionally, our primary focus was on depressive symptomatology and we expected that adolescents would have more direct access to information regarding their depressive moods and behaviors. This procedure has been used successfully in past research (e.g., Lewinsohn et al, 1993;Sheeber & Sorensen, 1998).Interviewers participated in a rigorous training program and demonstrated agreement with a senior interviewer (κ ≥ .80) on at least two interviews before conducting independent interviews. Interviewers included bachelor through doctoral level research staff.…”
mentioning
confidence: 99%